Guest

If the roots of ax2 + bx + c = 0 are in the ratio m : n, then (a) mna² = (m + n) c² (b) mnb² = (m + n) ac (c) mn b² = (m + n)² ac (d) mnb² = (m – n)² ac

If the roots of ax2 + bx + c = 0 are in the ratio m : n, then
(a) mna² = (m + n) c²
(b) mnb² = (m + n) ac
(c) mn b² = (m + n)² ac
(d) mnb² = (m – n)² ac

Grade:12th pass

1 Answers

Pawan Prajapati
askIITians Faculty 60796 Points
one year ago
Answer: c

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free